Actinomycosis of the Lower Lip: Report of a Case. (2nd August 2022) - Shigeoka, Manabu; Takeda, Daisuke; Akashi, Masaya
Abstract : Actinomycosis is usually a chronic infectious disease caused by Actinomyces species, which are anaerobic Gram-positive bacteria that normally colonize the human oral cavity and digestive and urogenital tracts. Although this lesion often occurs on soft tissue around the mandible, cases localized in the lip are very uncommon. We encountered a patient with actinomycosis in the lower lip. A 76-year-old woman with a 5-mm submucosal nodule of the lower lip was referred to our hospital from a dental clinic. The clinical diagnosis was a benign submucosal tumor. Total excision and histological examination were conducted. No oral antibiotic therapy was prescribed. The histological diagnosis was actinomycosis. The postoperative course was uneventful with no signs of recurrence during the 6 months after surgery.